Current and future glyphosate use in European agriculture - Neve, Paul; Matzrafi, Maor; Ulber, Lena; Baraibar, Bàrbara; Beffa, Roland; Belvaux, Xavier; Farré, Joel Torra; Mennan, Hüsrev; Ringselle, Björn; Salonen, Jukka; Soukup, Josef; Andert, Sabine; et al. (Wiley-Blackwell, 2024)
There has been a longstanding and contentious debate about the future of glyphosate use in the European Union (EU). In November 2023, the European Commission approved the renewal of the use registration for glyphosate for a further 10 years. Nevertheless, the EU Farm to Fork strategy calls for a 50% reduction in pesticide use by 2030. In November 2022, the European Weed Research Society organised a 2 day workshop to identify critical glyphosate uses in current EU cropping systems and to review the availability of glyphosate alternatives. Workshop participants identified four current, critical uses in EU cropping systems; control and management of perennial weeds, weed control in conservation agriculture, vegetation management in tree and vine crops and herbicide resistance management. There are few herbicide alternatives that provide effective, economic, broad-spectrum control of weeds, particularly perennial weeds. Mechanical weed control, and in particular, soil cultivation is the most obvious glyphosate alternative. However, this is not possible in conservation agriculture systems and, in general, increased soil cultivation has negative impacts for soil health. Emerging technologies for precision weed control can enable more targeted use of glyphosate, greatly reducing use rates. These technologies also facilitate the use and development of alternative targeted physical weed control (e.g. tillage, lasers, electricity), reducing the energy and environmental costs of these approaches. In tree crops, the use of organic and inorganic mulches can reduce the need for glyphosate use. In general, reduced use of glyphosate will require an even greater focus on integrated weed management to reduce weed establishment in agroecosystems, increase weed management diversity and limit the use of alternative resistance-prone herbicides.
Keywords: glyphosate; agriculture